Healthcare Mistreatment and Avoidance in Trans Masculine Adults: The Mediating Role of Rejection Sensitivity - Hughto, Jaclyn M.W. (Psychol Sex Orientat Gend Divers, 2018)
OBJECTIVES: Given that prior mistreatment can lead to heightened vigilance to and perceptions of future rejection, the present study examined whether this heightened vigilance, known as rejection sensitivity, mediates the association between healthcare mistreatment and healthcare avoidance in trans masculine (TM) adults. METHOD: Between 2015 and 2016, 150 TM adults completed a comprehensive survey assessing socio-demographics, sexual health, and healthcare experiences. A 5-item scale assessing participants’ sensitivity to rejection in healthcare scenarios was administered and psychometrically evaluated. Structural equation modeling was used to test whether rejection sensitivity in healthcare mediated the relationship between lifetime mistreatment in healthcare and past 12-month healthcare avoidance among TM adults. RESULTS: Overall, 68% of participants had experienced some form of mistreatment in healthcare in their lifetime and 43% had avoided healthcare in the past 12 months. For 5% of the sample, healthcare avoidance in the past 12 months resulted in a medical emergency. Path analyses revealed that healthcare mistreatment was positively correlated with rejection sensitivity and sensitivity was positively correlated with past 12-month healthcare avoidance. Rejection sensitivity mediated the relationship between mistreatment and healthcare avoidance (all p-values < 0.05). CONCLUSION: Rejection sensitivity may contribute to healthcare avoidance among stigmatized TM patients; however, longitudinal research is needed to establish the temporal ordering of these processes. Multilevel interventions to reduce healthcare discrimination and help TM adults cope with the psychological and behavioral consequences of stigma are recommended.